(untitled) (Research, Society and Development, 2020)
The present study evaluated the effects of 5-fluorouracil (5-FU) administration using a clinical treatment protocol for 14 days on the ileum in healthy Wistar rats. The animals were divided into two groups (n = 6/group): 5-FU-treated group and control group. The 5-FU group received 5-FU (15 mg/kg, i.p.) for 4 consecutive days, followed by a dose reduction to 6 mg/kg for 4 alternating days and then a last maintenance dose of 15 mg/kg on day 14. This treatment protocol is commonly used in the human clinical setting. The control group received saline (i.p.) according to the same treatment protocol. The ileum was then fractionated to evaluate oxidative stress parameters (catalase [CAT], superoxide dismutase [SOD], glutathione-S-transferase [GST], non-protein sulfhydryl groups [GSH], reactive oxygen species [ROS], and lipid hydroperoxide [LOOH]), markers of inflammation (interleukin-1 [IL-1], IL-6, myeloperoxidase [MPO], and N-acetylglucosaminidase [NAG]), and nitrite levels. HuC/D-immunoreactive myenteric neurons, neuronal nitric oxide synthase (nNOS)-immunoreactive nitrergic neurons, and ileum wall morphometry were also analyzed. The 5-FU treatment protocol promoted oxidative stress and altered nitrite levels but did not cause inflammation. The treatment protocol also reduced the density of nitrergic neurons and altered the morphometry of the general HuC/D-positive myenteric neuronal population and nNOS-positive nitrergic neuronal subpopulation. Treatment with the clinical 5-FU treatment protocol promoted grade I mucositis in rats, characterized by oxidative stress and morphological changes in the intestinal wall.